Hubungan Antara Keaktifan Berorganisasi Dengan Tingkat Perilaku Prososial Mahasiswa Pengurus PMII UNNES Tahun 2020 - Muchammad Badaruddin (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2021)
Based on the phenomenon that exists in the PMII UNNES student organization, it was found that the prosocial behavior of the members of PMII UNNES was good, but some of the administrators had low level of prosocial behavior when it comes in the outside of the organization. This research aims to determine the relationship between organizational contribution with the level of prosocial behavior. The technique used to collect the data is jenuh sampling. 63 members of the PMII UNNES year 2020 were the sample of this study. The data was collected by doing a pre-test and post-test using the organizational contribution scale and the prosocial scale. This research used correlational quantitative method with the correlation formula of 'product moment' named Pearson Correlation proposed by Karl Pearson. The result showed that the correlation coefficient (r) = 0.512 and p = 0.915> 0.05, which indicates that there is a positive and significant relationship between organizational contribution and the level of prosocial behavior done by the members of PMII UNNES year 2020.